Film as art - Arnheim, Rudolf (California : University of California Press, 1957)
"In the fall of 1957 the University of California Press expanded Arnheim's 1933 book "Film" by four essays and brought that landmark work back into print as "Film as Art". Now nearly fifty years after that re-edition, this book continues to occupy an important place in the literature of film. Arnheim's method, provocative in this age of technological wizardry, was to focus on the way art in film was derived from that medium's early limitations: no sound, no color, and no three-dimensional depth."--
Keywords: Motion pictures; Motion pictures -- Aesthetics